Escherichia coli Isolates Associated with Uncomplicated and Complicated Cystitis and Asymptomatic Bacteriuria Possess Similar Phylogenies, Virulence Genes, and O-Serogroup Profiles - Takahashi, Akira (American Society for Microbiology, 2006)
The genetic and serological characteristics of Escherichia coli isolates from patients with uncomplicated cystitis (UC), complicated cystitis (CC), and complicated asymptomatic bacteriuria (CASB) were determined. Phylogenetic group B2 was predominant in all categories. The prevalences of 14 out of 18 virulence factor genes were similar among the three categories, while pap, iha, ompT, and PAI were more frequently seen in isolates associated with UC than CC or CASB.